First record of cricket genus Caconemobius (Grylloidea: Nemobiinae) from China with description of a new species - Ma, Libin; Zhang, Tao; Qi, Tao (Zootaxa, 2015)
Caconemobius are distributed on widely separated islands in the Pacific area. Wings are absent in these species. They live among the rocks along the seashore, including the Hawaii, Japan and Korea. This genus is presently represented by 14 species worldwide. We found the first species of Caconemobius from China on the coast of Guangzhou. One new species, Caconemobius dibrachiatus Ma and Zhang, sp. nov., is described and illustrated.